Utilization Factors of Prevention Mother to Child HIV Transmission (PMTCT) Program Among Pregnant Women - Sitohang, Marya Yenita (Journal of Indonesian Social Sciences and Humanities, 2017)
HIV transmission patterns had changed from high-risk groups to the group of housewives. Housewives will get pregnant and give birth. The possibility of a child contracting HIV from his mother can be prevented by utilizing the PMTCT program optimally. The objective of this research is to analyze the internal and external factors of PMTCT program utilization for pregnant women. This research used a critical review of previous studies (2009-2017). Social structures (education, occupation, and economic status) were not significantly related to the behavior of PMTCT program utilization. However, the availability of information and consultation with health officers (external factors) related to knowledge and perception of pregnant women about HIV and PMTCT program (internal factors). Good knowledge and perception would connect with the behavior of PMTCT program utilization. Negative stigma (external factor) from the family, community, and health officer made pregnant women reluctant to utilize the PMTCT program optimally. In conclusion, the need for increasing the quality of health services to become client-oriented as of widening the scope and optimization of the PMTCT program.